Kendo as soft power and its role in Japan's cultural diplomacy with the Philippines - Bautista, Roehl Niño
Kendo is a Japanese armed martial art that has its roots back to samurai swordsmanship. Although it has diffused globally both as a sport and martial art, there has been a dearth of scholarship written on the historic development of kendo, particularly in the Philippines. The increasing number of kendo clubs between 2010 and 2019, and the establishment of a national federation in 2016 indicate that kendo is currently growing in the country.